Estimation of Irrigation Water Requirement for Paddy Cultivation in Parts of Hirakud Command Area, Orissa, Using RS & GIS Techniques - Chopra, Narayan (National Geographical Journal of India, 2022)
In this study an attempt has been made to extract information on water demand for paddy at the distributary level. An estimation of Irrigation water requirement for paddy cultivation in the central part of the Hirakund Command Area towed by distributaries Babebira and Bugbuga with command area of 1662 ha and 1211 ha respectively was carried out using remote sensing & meteorological data in a GIS environment. The overall irrigation water requirement when considering an average irrigation application efficiency of 85% were estimated for Baberia Distributory & Bugbuga Distributory for the month of January, Feburary & March. Irrigation water requirement highly correlated with crop water requirement due to absence of monsoon during rabi season in the study area. The present study establishes the importance of Geospatial Technology in estimation of crop water requirement and irrigation water requirement.